Health accounts from past to present for a political arithmetic - Magdalena Rathe; Patricia Hernández; Cornelis Van Mosseveld; Claudia Pescetto; Nathalie Van de Maele (Pan American Health Organization, 2018)
This report traces the progressive expansion of health accounts (HA) to measure national health expenditures, from the first attempts in 1926 by the American Medical Association to the present day. Milestones in the development of A System of Health Accounts (SHA) are covered, from the economic background to initial efforts by a few countries and organizations, to the need for a set of accounting standards for health care systems, and finally, to consolidation with SHA 2011. International organizations, such as the World Health Organization, Organization for Economic Cooperation and Development, Eurostat, the World Bank, and the United States Agency for International Development have been critical to expanding national HA exercises and ensuring that these are standardized, comparable, and become institutionalized. National efforts to track health expenditures have not only enriched collective results, but have become an important component of global leadership, informing policy the world over. More than 100 countries have created HA under the global standard and have gained a better understanding of health spending and financial flows. These results are key for monitoring progress toward national and global initiatives, such as the Sustainable Development Goals and Universal Health Coverage. Challenges remain to be tackled, among them institutionalization and quality of results. Social responsibility for improving data sources and expanding the generation and usability of health accounts are also needed.